(untitled) (Journal of Universal Science Research, 2025)
This article explores the pragmalinguistic functions of fearinducing lexical units in detective discourse, comparing Uzbek (Shaytanat) and English (Sherlock Holmes) literary traditions. The study examines how linguistic tools evoke fear, analyzing semantic, syntactic, and pragmatic strategies. The findings reveal cultural and linguistic distinctions in fear representation, highlighting the role of context, metaphor, and speech acts.